Qaraqalpaq juwap aytıslarınıń janrlıq hám kórkemlik ózgeshelikleri - Bazarbaeva, B (SCIENCE and SOCIETY, 2022)
In the article, one of the richest samples of the Karakalpak people, the genre and artistic features of juwap aytis are
Keywords: folklore; "aytis"; creativity; artistry; genre features